Introduction to PowerPoint 2010 - Conway, Pamela; Safari eBooks ([S.l.] : CompuWorks, 2012)
"This course will provide you with the skills you need to create effective and robust presentations in Microsoft PowerPoint 2010. After an introduction to PowerPoint's window components and Help system, students will learn to create, save, and rearrange presentations. The features required to format text, use drawing objects, work with graphics, and insert tables and charts will be covered, in addition to learning to use templates and themes, slide masters, and transition effects. Finally, students will learn to proof, run, and print presentations."--Resource description page.
Title from title screen.
Publication information from resource description page (viewed Apr. 8, 2013).
Presenter, Pamela Conway.
Keywords: Presentation graphics software; Microsoft PowerPoint (Computer file); Electronic books